The effects of leaf size and microroughness on the branch‐scale collection efficiency of ultrafine particles. Issue 8 (18th April 2015) - Huang, C. W.; Lin, M. Y.; Khlystov, A.; Katul, G. G.
Abstract Wind tunnel experiments were performed to explore how leaf size and leaf microroughness impact the collection efficiency of ultrafine particles (UFP) at the branch scale. A porous media model previously used to characterize UFP deposition onto conifers (Pinus taeda and Juniperus chinensis) was employed to interpret these wind tunnel measurements for four different broadleaf species (Ilex cornuta, Quercus alba, Magnolia grandiflora, and Lonicera fragrantissima) and three wind speed (0.3–0.9 ms−1) conditions. Among the four broadleaf species considered, Ilex cornuta with its partially folded shape and sharp edges was the most efficient at collecting UFP followed by the other three flat‐shaped broadleaf species. The findings here suggest that a connection must exist between UFP collection and leaf dimension and roughness. This connection is shown to be primarily due to the thickness of a quasi‐laminar boundary layer pinned to the leaf surface assuming the flow over a leaf resembles that of a flat plate. A scaling analysis that utilizes a three‐sublayer depositional model for a flat plate of finite size and roughness embedded within the quasi‐laminar boundary layer illustrates these connections. The analysis shows that a longer leaf dimension allows for thicker quasi‐laminar boundary layers to develop. A thicker quasi‐laminar boundary layer depth in turn increases the overall resistance to UFP deposition due to an increase in the diffusional path length thereby reducing the leaf‐scale UFP collection efficiency. It is suggested that the effects of leaf microroughness are less relevant to the UFP collection efficiency than are the leaf dimensions for the four broadleaf species explored here.